Determinants of telemarketers: a case study at KFC Holding International College (JB Campus) / Noor Syazwani Sulaiman - Sulaiman, Noor Syazwani (2014)
This paper is about a research on the determinants of telemarketers: a case study at KFCH International College in a qualitative research mode, researcher used face to face interview, informal interview, and observation in order to get the information on the traits of a good telemarketer and how does KFCH International College (KFCIC) practicing it in daily basis. From the interview, researcher identified some of the criteria was not practiced properly in the company. However, for the crucial criteria, telemarketers in KFCHIC actually practiced some of them but it seems like there are gaps between actual result and theoretical evidence from previous research. Following these findings, the paper started with an overview of company background, follow by the literature review, research methodology, findings analysis and finally conclusions and recommendation.